Effect of farnesol on Candida dubliniensis morphogenesis - Henriques, Mariana (2007)
Cell–cell signalling in Candida albicans is a known phenomenon and farnesol was identified as a quorum sensing molecule determining the yeast morphology. The aim of this work was to verify if farnesol had a similar effect on Candida dubliniensis, highlighting the effect of farnesol on Candida spp. morphogenesis. Methods and Results: Two different strains of C. dubliniensis and one of C. albicans were grown both in RPMI 1640 and in serum in the presence of absence of farnesol. At 150 μmol l -1 farnesol the growth rate of both Candida species was not affected. On the contrary, farnesol inhibited hyphae and pseudohyphae formation in C. dubliniensis. Conclusion: Farnesol seems to mediate cell morphology in both Candida species. Significance and Impact of the Study: The effect of farnesol on C. dubliniensis morphology was not reported previously.